CONTRIBUTION OF TECHNOLOGY ENHANCED LEARNING TO THE INCLUSION OF STUDENTS WITH SPECIAL EDUCATION NEEDS - Rutkiene, Ausra; Greenspon, Rasa (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Students with special educational needs (henceforth, SEN) are usually separated from traditional educational settings; thus, risk of being completely excluded from educational activities due to their physical or mental limitations is increased and access to education can be reduced significantly. Thus, a problem arises that students with SEN have restricted possibilities to participate in study process and to obtain desired qualifications together with non-disabled students; therefore, they may feel excluded from education system. The aim of the research is to evaluate how technology enhanced learning (henceforth, TEL) contributes to reducing exclusion of students with SEN. In order to achieve the aim, qualitative research methodology has been applied. Data has been selected during semi-structured interviews and analyzed by applying a qualitative content analysis. Research participants are graduate students with SEN who are currently engaging themselves in study process fostered by TEL at U.S. universities. The research has provided the following findings: TEL increases accessibility of education by eliminating social and physical barriers, enabling constant movement, and helping students with SEN cope with their impairments. TEL can be the only way for learners to complete their education. The research has not indicated that TEL can ensure inclusion. However, TEL enables students with SEN to receive qualifications and degrees in a much more convenient way.